Leveraging Government Policies and Schemes for Promoting Mushroom Entrepreneurship in India - Shirur, Mahantesh; Gummagolmath , KC; Singh, Manjit (Mushroom Research, 2021)
In recent times, there is increased emphasis on the nutritional security across globe including India. Mushroom as a nutritional food has a major role to play to complement the national efforts to address the hunger and malnourishment. Mushroom entrepreneurship to grow in the country, there is a need for an enabling environment and policy backing to incentivize private individuals to take up the mushroom entrepreneurship. There are several policies and schemes by the federal and provincial Governments in India that help to attract the entrepreneurs to invest in mushroom farming. There is a need for consistent popularization of these policies and schemes among the entrepreneurs so that they make full use of the opportunity of these initiatives by the Government to venture into mushroom enterprises. This article makes an effort to comprehensively discuss the Government policies and schemes to sensitise the entrepreneurs about the schemes and ways to apply them in the mushroom entrepreneurship.